A Buddhist Economic Lens on Bank Stability: Empirical Analysis of Nepalese Commercial Banks - Bista, Purushotam (Journal of Kathmandu BernHardt College, 2025)
This study, grounded in Buddhist economic values of ethical prudence and sustainability, investigates the determinants of bank stability in Nepal, focusing on capital adequacy, loan risk (Non-performing Loans -NPL) bank size, gross domestic product (GDP) growth, and inflation. Using descriptive analysis and data from Everest Bank Limited and Nabil Bank Limited, it reveals that capital adequacy plays the most critical role in ensuring financial resilience, affirming findings and robust capital buffers are vital for absorbing economic shocks. Loan risk, particularly non-performing loans, also exerts a significant negative impact on stability, highlighting the Buddhist principle of mindful lending and the need for sound credit risk management. Other factors such as bank size, GDP growth, and inflation were found to have statistically insignificant effects, suggesting that in Nepal’s context, internal financial discipline outweighs external macroeconomic variables in driving stability. The study's insights not only contribute to academic discourse but also offer practical guidance for policymakers and banking institutions committed to fostering a resilient and ethically grounded financial system.